Prevalence of duodenal ulcer and associated Helicobacter pylori infection in chronic liver disease - Nanda, Rajesh A.; George, Melvin (International Journal of Research in Medical Sciences, 2020)
Background: Aim was to determine the prevalence of duodenal ulcer (DU) and associated H. pylori infection in patients with liver cirrhosis. Methods: A prospective observational study was conducted at a tertiary care medical college hospital and research center in Suburban Chennai, Southern India, where consecutive patients with cirrhosis of liver undergoing UGI endoscopy were screened for duodenal ulcer and in those with duodenal ulcer H. Pylori testing was performed with RUT and histology of antral biopsy specimen. Prevalence was compared with age and socioeconomic status matched control population who presented with dyspepsia and underwent UGI endoscopy during the study period. Results: Total 106 patients with chronic liver disease and 481 matched non cirrhotics with dyspepsia underwent UGI endoscopy during the study. Duodenal ulcer was diagnosed in 19.08% patients with cirrhosis and in 6.02% non-cirrhotic patients with dyspepsia.16.66% patients with DU in chronic liver disease (CLD) group were diagnosed to have H. Pylori infection by histology and RUT in comparison to 93.1% H. Pylori infection in control population with DU. Conclusions: The incidence of DU in CLD was significantly higher when compared to general population with dyspepsia. However, majority of patients with PUD in cirrhosis of liver did not have associated H. Pylori infection. Increased incidence of DU in CLD is probably due to several other mechanisms related to portal hypertension. Routine treatment with anti H. Pylori regime may not be warranted with CLD patients with DU, therefore a test and treat strategy for H. Pylori will be more optimal in CLD.